Chemoselective calcium-catalysed direct amidation of carboxylic esters1. Issue 95 (15th October 2015) - Nguyen, D. Thao; Lenstra, Danny C.; Mecinović, Jasmin
<x xml:space="preserve">Abstract</x> Cheap, non-toxic and environmentally benign CaI2 catalyses direct amide bond formation between unactivated carboxylic esters and primary amines in excellent yields.